Emerging Role of the Autophagy/Lysosomal Degradative Pathway in Neurodevelopmental Disorders With Epilepsy - Fassio, Anna; Falace, Antonio; Esposito, Alessandro; Aprile, Davide; Guerrini, Renzo; Benfenati, Fabio (Frontiers in Cellular Neuroscience, 2020)
Autophagy is a highly conserved degradative process that conveys dysfunctional proteins, lipids and organelles to lysosomes for degradation. The post-mitotic nature, complex and highly polarized morphology and high degree of specialization of neurons make an efficient autophagy essential for their homeostasis and survival. Dysfunctional autophagy occurs in aging and neurodegenerative diseases and autophagy at synaptic sites seems to play a crucial role in neurodegeneration. Moreover, a role of autophagy is emerging for neural development, synaptogenesis and the establishment of a correct connectivity. Thus, it is not surprising that defective autophagy has been demonstrated in a spectrum of neurodevelopmental disorders, often associated with early onset epilepsy. Here we discuss the multiple roles of autophagy in neurons and the recent experimental evidence linking neurodevelopmental disorders with epilepsy to genes coding for autophagic/lysosomal system-related proteins and envisage possible pathophysiological mechanisms ranging from synaptic dysfunction to neuronal death.